The role of media literacy in the public relations: What is happening in the portuguese universities? - Mourão, Rita Monteiro (2020)
Media literacy has a key role in education. It is known that the public relations profession often involves a position of media relations. In this context, this type of expert must obtain skills in the critical and active use of media. Afterwards it arises the need to understand what kind of investment in media literacy has been done by Portuguese Public Universities. This will be the objective of this exploratory qualitative study. For the collection of information, we have proceeded to the analysis of the curricula of Degree’s and master’s degree in Public Relations courses of 15 Portuguese Public Universities. In general, it was concluded that there is still little investment at this level. Of the 15 Portuguese public universities analyzed, only three universities hold courses on media education in their curricula, within the degree in public relations / organizational communication / strategic communication. Regarding to the master’s degree we found that only four of the 15 Portuguese Public Universities consider the media literacy in their curricula. This research focuses specifically in Public Universities. However, in future studies it will be also important to include private universities to compare the main differences.